Disclosure of Corporate Social Responsibility on Corporate Financing Constraints with Financial Transparency Moderating Variables - Jingga Novebreza Islah (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2021)
This study aims to determine the effect of corporate social responsibility on corporate financing constraints with financial transparency as a moderating variable. The sample used in the manufacturing sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period as many as 89 companies were selected using a purposive sampling technique. This study uses panel data regression analysis and moderated regression analysis (MRA). The results of the study indicate that corporate social responsibility affects corporate financing constraints. Meanwhile, the variety of corporate social responsibility which is moderated by financial transparency affects corporate financing constraints. In addition, the control variable of company age also affects the corporate financing constraint, while the growth variable does not affect the corporate financing constraint.